Why aren't Jewish women circumcised? : gender and covenant in Judaism - Cohen, Shaye J. D. (S. Mark Taper Foundation imprint in Jewish studies., 2005)
Why aren't Jewish women circumcised? This improbable question, first advanced by anti-Jewish Christian polemicists, is the point of departure for this wide-ranging exploration of gender and Jewishness in Jewish thought. With a lively command of a wide range of Jewish sources--from the Bible and the Talmud to the legal and philosophical writings of the Middle Ages to Enlightenment thinkers and modern scholars--Shaye J.